A Randomized Clinical Trial of Standard versus Expanded Cultures to Diagnose Urinary Tract Infections in Women. Issue 5 (29th November 2021) - Barnes, Hayley C.; Wolff, B.; Abdul-Rahim, O.; Harrington, A.; Hilt, E. E.; Price, T. K.; Halverson, T.; Hochstedler, B. R.; Pham, T.; Acevedo-Alvarez, M.; Joyce, C.; Fitzgerald, C. M.; et al.
Abstract : Purpose: We compared urinary tract infection (UTI) symptom resolution rates at 7–10 days in symptomatic women randomized to treatment based on standard urine culture (SUC) versus expanded quantitative urine culture (EQUC) results. Materials and Methods: Women ≥18 years old who responded "yes" to "do you feel you have a UTI?" agreed to urethral catheterization and followup. Symptoms were assessed using the validated UTI Symptom Assessment (UTISA) questionnaire. Culture method was randomized 2:1 (SUC:EQUC); antibiotics were prescribed to women with positive cultures. The primary outcome, UTI symptom resolution, was determined 7–10 days following enrollment on all participants regardless of treatment. Results: Demographic data were similar between groups. Of the SUC and EQUC groups 63% and 74% had positive cultures (p=0.10), respectively. Of participants with positive cultures 97% received antibiotics. Primary outcome data were provided by 215 of 225 participants (SUC 143 [95%], EQUC 72 [97%]). At the primary outcome assessment, 64% and 69% in the SUC and EQUC groups, respectively, reported UTI symptom resolution (p=0.46); UTISA scores improved from baseline in the EQUC arm compared to the SUC arm (p=0.04). In the subset of women predominated by non- Escherichia coli (76), there was a trend toward more symptom resolution in the EQUC arm (21%, p=0.08). Conclusions: Symptom resolution was similar for the overall population ( E. coli and non- E. coli ) of women treated for UTI symptoms based on SUC or EQUC. Although the sample size limits conclusions regarding the utility of EQUC in women with non- E. coli uropathogens, the detected trend indicates that this understudied clinical subset warrants further study.